2015
DOI: 10.1615/interfacphenomheattransfer.2016014779
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Phenomena and Heat Transfer in Proton Exchange Membrane Fuel Cells

Abstract: Water transport and heat transfer are two critical issues for proton exchange membrane fuel cell (PEMFC) commercialization. Proper water and heat management ensure a sufficient reactant transport to reaction sites and high operating temperature, which requires good understanding of water and heat transport in PEMFCs. In this paper, previous studies about interfacial phenomena related to water transport and heat transfer in PEMFCs are reviewed. The interfacial phenomena in different components are discussed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 268 publications
(333 reference statements)
0
13
0
Order By: Relevance
“…However, this assumption is not that accurate considering the influence of liquid water in flow field on gas supply from flow field to porous electrodes. As we all know, the two‐phase flow in the whole PEMFC has a very significant influence; at this point, Liu et al has reviewed the detailed two‐phase interfacial phenomena in PEMFC. However, coupling the complete two‐phase interfacial phenomena with electrochemical reactions in PEMFC is still hard to achieve .…”
Section: Introductionmentioning
confidence: 99%
“…However, this assumption is not that accurate considering the influence of liquid water in flow field on gas supply from flow field to porous electrodes. As we all know, the two‐phase flow in the whole PEMFC has a very significant influence; at this point, Liu et al has reviewed the detailed two‐phase interfacial phenomena in PEMFC. However, coupling the complete two‐phase interfacial phenomena with electrochemical reactions in PEMFC is still hard to achieve .…”
Section: Introductionmentioning
confidence: 99%
“…Fontana et al used the volume of fluid method to study liquid water transport behaviors in a tapered flow channel based on a 2D dynamic model, and Mancusi et al further investigated the influence of the taper angle with a 3D fuel cell model, and both studies found that the tapered flow channel significantly influences liquid water transport and removal in the flow channel. Liu et al emphasized that the volume of fluid method is mainly used to investigate liquid water dynamics, and comprehensive model that contains complex interfacial phenomena and large physical size should be further studied in PEM fuel cell. And they further developed a visualization equipment to observe the two‐phase flow in the flow channel during the mode switching of fuel cell.…”
Section: Introductionmentioning
confidence: 99%
“…As the solar cell can work again in sufficient of solar energy, the cell is switched from discharging to charging mode for accumulating hydrogen energy and for lifetime support. Occupying superiorities of low emission and being free from self‐discharge, researches on URFCs are ulteriorly expanded in terrestrial applications, such as renewable energy, portable power supply, and electric vehicle.…”
Section: Introductionmentioning
confidence: 99%